(untitled) (Research, Society and Development, 2020)
This study aims to organize the observable characteristics of post-critical patients in order to form standards of conformity or non-compliance to be used in performance evaluations in the quality control of health care production in intensive care units. Having hypothesized that the existence of different observable characteristics of post-critical patients determines patterns of intensity of patient defects, due to the progression of disease deterioration, even after critical care, which will require the development of different nursing services in the long term. This is a descriptive-exploratory study, with a qualitative approach, carried out in three phases: literature review, construction of attributes and their sublevels and organization of attributes and their levels. From the scientific literature, the classification of the observable characteristics of post-critical patients was elaborated, weighted by the intensity of the "defect" of clinical deterioration. Soon after, the tree diagram of the clinical dimension used to organize the attributes and their levels was elaborated, and later, an attribute was extracted as an example to illustrate the application of the tree diagram in practice. Therefore, 9 attributes were elaborated with stratification from 3 to 8 levels, totaling 39 levels. It was evidenced that it is possible to group the observable characteristics of post-critical patients by different intensities of patterns of defects due to the progression of disease deterioration, even after patients have undergone critical care, which will require the development of different nursing services in the long term.